Protein crystallography and fragment-based drug design. (June 2013) - Caliandro, Rocco; Belviso, Danilo Benny; Aresta, Brunella Maria; de Candia, Modesto; Altomare, Cosimo Damiano
Crystallography is a major tool for structure-driven drug design, as it allows knowledge of the 3D structure of protein targets and protein–ligand complexes. However, the route for crystal structure determination involves many steps, some of which may hamper its high-throughput use. Recent efforts have produced significant advances in experimental and computational tools and protocols. They include automatic crystallization tools, faster data collection devices, more efficient phasing methods and improved ligand-fitting procedures. The timescales of drug-discovery processes have been also reduced by using a fragment-based screening approach. Herein, the achievements in protein crystallography over the last 5 years are reviewed, and advantages and disadvantages of the fragment-based approaches to drug discovery that make use of x-ray crystallography as a primary screening method are examined. In particular, in some detail, five recent case studies pertaining to the development of new hits or leads in relevant therapeutic areas, such as cancer, immune response, inflammation, metabolic syndrome and neurology are described.